2018
DOI: 10.1002/ejic.201800092
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Electrochemical Properties of O‐Alkyldithiophosphato Nickel Complexes with Chelating Aminodiphosphine Ligands

Abstract: Eight new O-alkyldithiophosphato nickel complexes 1-8 with chelating aminodiphosphine ligands have been successfully synthesized in moderate yields by the treatment of O,O′-alkydithiophosphoric acid salts (R 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…[10][11][12][13][14] Notably, diphosphine ligand is widely used in the design of complex catalysts for hydrogen revolution because of its significant advantage in terms of ease of modification to tune catalytic actives. [15][16][17][18][19] 1,1'-Bis(diphenylphosphino)ferrocene (dppf), as a well-known sterically restrictive ligand, has been used to synthesize dppf-supported nickel complexes that perform hydrogen evolution catalysts with low overpotentials. [20,21] Meanwhile, Xie and co-workers reported that dcpf-supported nickel complexes containing O-alkyldithiophosphate ligands, [(dcpf)Ni(S 2 P{O}OR)] (dcpf = 1,1-bis (dicyclohexylphosphino)ferrocene), present higher electrocatalytic performances for the reduction trifluoroacetic acid (TFA) to hydrogen with turnover frequencies of 1047-2545 s À 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14] Notably, diphosphine ligand is widely used in the design of complex catalysts for hydrogen revolution because of its significant advantage in terms of ease of modification to tune catalytic actives. [15][16][17][18][19] 1,1'-Bis(diphenylphosphino)ferrocene (dppf), as a well-known sterically restrictive ligand, has been used to synthesize dppf-supported nickel complexes that perform hydrogen evolution catalysts with low overpotentials. [20,21] Meanwhile, Xie and co-workers reported that dcpf-supported nickel complexes containing O-alkyldithiophosphate ligands, [(dcpf)Ni(S 2 P{O}OR)] (dcpf = 1,1-bis (dicyclohexylphosphino)ferrocene), present higher electrocatalytic performances for the reduction trifluoroacetic acid (TFA) to hydrogen with turnover frequencies of 1047-2545 s À 1 .…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Meanwhile, Xie and co-workers reported that dcpf-supported nickel complexes containing O-alkyldithiophosphate ligands, [(dcpf)Ni(S 2 P{O}OR)] (dcpf = 1,1-bis (dicyclohexylphosphino)ferrocene), present higher electrocatalytic performances for the reduction trifluoroacetic acid (TFA) to hydrogen with turnover frequencies of 1047-2545 s À 1 . [22] In addition, bis(diphenylphosphine)amine (RN(PPh 2 ) 2 , PNP) has also been used in the fabrication of complex electrocatalysts for hydrogen evolution, such as [(RN(PPh 2 ) 2 )Ni(S 2 P{O}OR')], [18] [Fe 2 (μpdt)(CO) 4 {(μ-Ph 2 P) 2 NR], [19] [(RN(PPh 2 ) 2 )Ni(mnt)], [23] and [(RN-(PPh 2 ) 2 )Ni(bdt)] [24,25] (pdt = propylene-1,3-dithiolate, mnt = maleonitriledithiolate, and bdt = 1,2-benzenedithiolate).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previously reported researches, [33,40,47] two possible different pathways for the formation of 1-5 can be proposed. For the synthetic method I, as depicted in Scheme 3, the mechanism is believed to proceed firstly by the nucleophilic attack of the negative charged sulfur atom of the (CH 3 O) 2 P{S}S À anion on the nickel atom of the nickel complex [RN(PPh 2 )({S}PPh 2 )]NiCl 2 to give an tetra-coordinated intermediate I A .…”
Section: General Featuresmentioning
confidence: 99%
“…Especially recently, the aminodiphosphine nickel complexes with the 1,2-benzenedithiolate or O-alkyldithiophosphate ligand, which all form a four-membered [Ni(PNP)] metallocycle from the aminodiphosphine ligand, have been successfully used as electrocatalysts for the reduction proton to hydrogen. [40][41][42] Fliedel and coworkers have reported a series of aminodiphosphine monosulfide RN(PPh 2 )({S}PPh 2 ) compounds and their nickel complexes, in which the ligand is an asymmetrical P,P S heterobidentate ligand and brings about stereoelectronic differentiation within the nickel coordination sphere, especial in the position trans to the donor atom. [43,44] In contrast to [RN(PPh 2 ) 2 ]NiCl 2 , [(RN(PPh 2 ) ({S}PPh 2 ))NiCl 2 forms a five-membered [Ni(SPNP)] metallocycle and exhibits a solvent dependent reversible ligand exchange in solution.…”
Section: Introductionmentioning
confidence: 99%
“…In general, mercaptans are the common reagent adopted to react with carbonyl iron to give butterfly Fe/S cluster, and the products dinuclear iron carbonyl complexes can be obtained in satisfactory yields. As the analogue of mercaptan, dialkyldithiophosphate can also be used as the source of SH due to their similar structural features, and the reaction of Fe 3 (CO) 12 with dialkyldithiophosphate has not been studied so far. We launched the study of the direct reaction of O,O ′‐dialkyldithiophosphate diethylamine salts with Fe 3 (CO) 12 .…”
Section: Introductionmentioning
confidence: 99%